A Review : Pengembangan Obat Rheumatoid Arthritis (RA) dengan Berbagai Pendekatan - Amelia, Ferda; Kaniawati, Marita; Gabriela Da Costa Soares, Fidelia s; Languwila, Indrawati; Dwi Fatma, Ira; Jefry, Jefry; Efraim Lian, Kevin; Irene Welmince Bokotei, Martini; Taofiq Putra Pratama, Muhamad; Septri Rahmawati, Nabila; Kasihtheisya, Naida; Subakti, Nanda; Dodit Rinaldi, Muhammad (Jurnal Medika Farmaka, 2025)
Introduction: Rheumatoid Arthritis (RA) is an autoimmune disease characterized by chronic inflammation of the joints, which can lead to cartilage damage and disability. Not all standard medications for RA therapy are efficient for all patients and long-term use can cause serious side effects. Therefore, it is necessary to develop drugs for RA involving various approaches, both pharmacological and non-pharmacological. Method: This article review is based on references to several articles from online databases published nationally and internationally. Result: From the article search, there were 10 articles discussing RA drug development from various approaches. Conclusion: Based on the review of articles carried out, there is drug development using a pharmacological approach including the use of natural ingredients such as purslane tea, red betel leaf extract, secang plants and curcumin, nanotechnology-based innovations such as composite hydrogel and MTX nanocarriers, a drug repurposing approach to the discovery of new drugs alpha-linolenic acid and Belatacept as well as non-pharmacological approaches with complementary therapies such as red ginger and warm betel compresses. Keywords: Drug development, treatment, rheumatoid arthritis